109k views
5 votes
Simplify 4/5plus 6 minus(3/9 plus 4

2 Answers

6 votes

Answer:

157/150

Explanation:

We have given :

4/5+6-3/9+4

We have to simplify this expression.

4/5+6-3/9+4 = 4/5-1/3+10

The LCM of this expression is 15.

Multiply each term by 15 we get,

(12-5+150)/15

(7-150)/15

157/150 is the simplification.

User Jrsm
by
5.8k points
2 votes

Answer:

Final answer is
(157)/(15)

Explanation:

Given expression is


(4)/(5) +6-(3)/(9) +4

Now we need to simplify that.


(4)/(5) +6-(3)/(9) +4


=(4)/(5)+6-(1)/(3)+4


=(4)/(5)-(1)/(3)+10


=(4)/(5)\cdot(3)/(3)-(1)/(3)\cdot(5)/(5)+10\cdot(15)/(15)


=(12)/(15)-(5)/(15)+(150)/(15)


=(12-5+150)/(15)


=(7+150)/(15)


=(157)/(15)

Hence final answer is
(157)/(15)

User LauraNMS
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.